2000
DOI: 10.1557/proc-629-ff8.7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Contamination on Adhesive Forces as Measured by Contact Mechanics

Abstract: The contact adhesive forces between two surfaces, one being a soft hemisphere and the other being a hard plate, can readily be determined by applying an external compressive load to mate the two surfaces and subsequently applying a tensile load to peel the surfaces apart. The contact region is assumed the superposition of elastic Hertzian pressure and of the attractive surface forces that act onIy over the contact area. What are the effects of the degree of surface contamination on adhesive forces? Clean alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…When the silanol end groups were replaced by reaction with hexamethyldisilazane (which replaces the end-group with a trimethylsilyl group), the hysteresis was reduced by up to 80%. In contrast, Emerson et al [30] demonstrated that the presence of SiH groups was not required for hysteresis to occur between toluene-extracted hemispheres. Unreacted SiH groups were removed by reaction with ethylene gas, but hysteresis was still observed.…”
Section: Introductionmentioning
confidence: 91%
“…When the silanol end groups were replaced by reaction with hexamethyldisilazane (which replaces the end-group with a trimethylsilyl group), the hysteresis was reduced by up to 80%. In contrast, Emerson et al [30] demonstrated that the presence of SiH groups was not required for hysteresis to occur between toluene-extracted hemispheres. Unreacted SiH groups were removed by reaction with ethylene gas, but hysteresis was still observed.…”
Section: Introductionmentioning
confidence: 91%
“…This higher adhesion is expected, given that polyimide typically exhibits a lower surface energy than the native oxide on the surface of aluminum. A total solid surface energy of approximately 40 mJ/m 2 has been measured for polyimide [70], while aluminum oxide has range of values reported throughout the literature, ranging anywhere from 40 to 638 mJ/m 2 , depending on the surface preparation [71,72]. Luo and Wong report that the dispersive surface energy of UV/ozone-cleaned alumina is 45.9 mJ/m 2 [73].…”
Section: Adcb Testingmentioning
confidence: 99%